Ubiquitin Ser65 phosphorylation affects ubiquitin structure, chain assembly and hydrolysis. (20th December 2014) - Wauer, Tobias; Swatek, Kirby N; Wagstaff, Jane L; Gladkova, Christina; Pruneda, Jonathan N; Michel, Martin A; Gersch, Malte; Johnson, Christopher M; Freund, Stefan MV; Komander, David
Abstract: The protein kinase PINK1 was recently shown to phosphorylate ubiquitin (Ub) on Ser65, and phosphoUb activates the E3 ligase Parkin allosterically. Here, we show that PINK1 can phosphorylate every Ub in Ub chains. Moreover, Ser65 phosphorylation alters Ub structure, generating two conformations in solution. A crystal structure of the major conformation resembles Ub but has altered surface properties. NMR reveals a second phosphoUb conformation in which β5‐strand slippage retracts the C‐terminal tail by two residues into the Ub core. We further show that phosphoUb has no effect on E1‐mediated E2 charging but can affect discharging of E2 enzymes to form polyUb chains. Notably, UBE2R1‐ (CDC34), UBE2N/UBE2V1‐ (UBC13/UEV1A), TRAF6‐ and HOIP‐mediated chain assembly is inhibited by phosphoUb. While Lys63‐linked poly‐phosphoUb is recognized by the TAB2 NZF Ub binding domain (UBD), 10 out of 12 deubiquitinases (DUBs), including USP8, USP15 and USP30, are impaired in hydrolyzing phosphoUb chains. Hence, Ub phosphorylation has repercussions for ubiquitination and deubiquitination cascades beyond Parkin activation and may provide an independent layer of regulation in the Ub system. Synopsis: Ubiquitin phosphorylation by PINK1 kinase is involved in Parkin activation. Structural and biochemical work now shows that it also affects ubiquitin conformation, chain assembly and deconjugation, thus potentially affecting ubiquitin signaling more broadly. PINK1 phosphorylates Ser65 both in free ubiquitin and in polyubiquitin chains. Parkin is activated by phospho‐ubiquitin only in the presence of unphosphorylated ubiquitin. Ser65 phospho‐ubiquitin interconverts between a major, canonical ubiquitin conformation and a previously unknown minor conformation. Due to beta‐strand slippage, the ubiquitin C‐terminal tail is retracted in the minor conformation. Ser65 phospho‐ubiquitin is charged onto E2 enzymes, but discharging with and without E3 can be inhibited. Ser65 phospho‐ubiquitin‐incorporating polyubiquitin chains are less well hydrolyzed by all classes of DUB enzymes. Abstract : PINK1‐mediated ubiquitin phosphorylation is not only involved in Parkin activation, but has the potential to affect ubiquitin conjugation and signaling at various levels.